Reflections on the Governance of Calon Arang Performance: Between Contestation, Commodification, and Religion - Komang Indra Wirawan (Mudra Jurnal Seni Budaya, 2024)
Calon Arang performing arts have been developing very well recently. It is proved by the held of many Calon Arang performances and the hectic news coverage and related social media uploads. In addition to the audience being enthusiastic about the show, the artists also continue to innovate and be creative in presenting interesting performances. However, the existing Calon Arang art is a sacred performance that has undergone many commodifications and deviations. Furthermore, there was a lot of chaos and even death. Therefore, a management system for the Calon Arang performing arts is needed that is in accordance with tattwa (philosophy), susila (ethics), and upakara (rituals), but at the same time, it provides sufficient space for artists to express their creativity, and can still present interesting shows to the public. This research was organized in qualitative descriptive method to formulate what factors need to be used as the basis for the management of Calon Arang performance. The research result shows that the preparation of Calon Arang performance management guidelines was not an easy thing because there were conflicts in mapping out the parameters to be used as the basis for managing the Calon Arang Show, both from an aesthetic and religious point of view. However, it is hoped that with the cooperation of various parties, initial principles can be formulated on how to manage the Calon Arang show.